A Meta-Analytic Review of Social Identification and Health in Organizational Contexts. (November 2017) - Steffens, Niklas K.; Haslam, S. Alexander; Schuh, Sebastian C.; Jetten, Jolanda; van Dick, Rolf
We provide a meta-analytical review examining two decades of work on the relationship between individuals' social identifications and health in organizations (102 effect sizes, k = 58, N = 19, 799). Results reveal a mean-weighted positive association between organizational identification and health ( r = .21, T = .14). Analysis identified a positive relationship for both workgroup ( r = .21) and organizational identification ( r = .21), and in studies using longitudinal/experimental ( r = .13) and cross-sectional designs ( r = .22). The relationship is stronger (a) for indicators of the presence of well-being ( r = .27) than absence of stress ( r = .18), (b) for psychological ( r = .23) than physical health ( r = .16), (c) to the extent that identification is shared among group members, and (d) as the proportion of female participants in a sample decreases. Overall, results indicate that social identifications in organizations are positively associated with health but that there is also substantial variation in effect size strength. We discuss implications for theory and practice and outline a roadmap for future research.